OPTIMALISASI HASIL BELAJAR MATEMATIKA KELAS VII MELALUI VIDEO DI MASA PANDEMI COVID-19 - Sukarto, Sukarto; Abadiyah, Lilik Masluhatul (CV Sintesia, 2025)
Mathematical communication is a basic skill that must be mastered by students in learning mathematics. In learning mathematics, teachers are expected to be able to improve students' mathematical communication, especially during the covid 19 pandemic. Teachers are also expected to be able to convey material creatively. One of the efforts made by the teacher is the use of video. The purpose of this research is to describe the use of video in optimizing student learning outcomes in learning mathematics. The research method used is CAR. The research subjects were class VII students of MTs Al Fatah, Sidoarjo for the 2020/2021 academic year, totaling 43 students. The results of this research are the pre-cycle shows 52.9%), in the first cycle 27 students (61.7%), and in the second cycle, it reaches 37 students (86%). This proves that learning by using video improves students' mathematical learning outcomes.